Development of risk assessment tool for small scale gold mining in the Philippines - Bernaldez, Isachar P.; Soriano, Virginia Jose; Tamayao, Mili-Ann M. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
This study aimed at the possibility of developing a tool for a systematic examination and identification of the hazards on the small-scale gold mining industry in the Philippines. This study covered the evaluation of six types of hazards in a working environment, namely: safety-hazards, physical hazards, chemical and dust hazards, ergonomic hazards, biological hazards, and work organization hazards. The compliance was measured by using standards from occupational health and safety and DENR administrative order 97-30. The tool was used by the officials from Provincial Environmental Natural Resources Office (PENRO) and the small-scale gold miners from Abra, Benguet and Camarines Norte. Results showed that low compliance and violations are likely to be committed by miners from Abra and Camarines Norte due to lack of information regarding the standards set by government. Results also indicated that top hazards are dependent on the chosen process for extraction of ores (e.g. surface mining) and on the process of extracting gold (e.g. use of mercury). Furthermore, analysis from Cohen's kappa of the responses showed the difference of knowledge of miners and PENRO. Lastly, based on user evaluation, the risk assessment tool is found to be effective to PENRO, learnable and covers most hazards in small scale mining in the Philippines.
Thesis (M.S. Industrial Engineering)--University of the Philippines Diliman
Keywords: Gold mines and mining -- Philippines; Gold mines and mining -- Risk assessment